2020
DOI: 10.3390/molecules25030577
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and Comprehensive Chemical Profiling Study of Flavonoids and Phenolic Acids in the Aerial Parts of Allium Mongolicum Regel and Their Intestinal Motility Evaluation

Abstract: To clarify whether flavonoids and phenols in Allium mongolicum Regel have the effect of improving gastrointestinal function and analyze its quality, this study was designed to isolate and identify them from the aerial parts of A. mongolicum by using various chromatographic and spectrophotometric methods, a bioassay on motility of mouse isolated intestine tissue, as well as qualitative analysis using liquid chromatography/mass spectrometry (LC-MS) analysis. As a result, 31 flavonoids and phenolic acids were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Data for compound 11 : white powder, m. p. 142–144°C; ESI-MS: Calcd for C 15 H 18 O 9 ([M-H] - ), 341.17; 1 H NMR (400 MHz, DMSO- d 6 ) δ : 7.55 (d, J = 15.8 Hz, 1H, H-7), 7.08 (d, J = 2.1 Hz, 1H, H-2), 7.01 (dd, J = 8.2, 2.0 Hz, 1H, H-6), 6.78 (d, J = 8.2 Hz, 1H, H-5), 6.26 (d, J = 15.9 Hz, 1H,H-8), 5.45 (d, J = 7.9 Hz, 1H), 5.28 (s, 1H), 5.06 (s, 2H,H-6′), 4.58 (s, 1H), 3.69–3.62 (m, 2H), 3.31–3.10 (m, 6H); 13 C NMR (100 MHz, DMSO- d 6 ) δ : 165.39 (C-9), 148.81 (C-4), 146.47 (C-7), 145.70 (C-3), 125.42 (C-1), 121.74 (C-6), 115.86 (C-5), 114.91 (C-8), 113.41 (C-2), 94.31 (C-1′), 77.86 (C-5′), 76.52 (C-3′), 72.56 (C-2′), 69.60 (C-4′), and 60.67 (C-6′). According to the abovementioned data and literature ( Dong et al, 2020 ), compound 11 was identified as 1-Caffeoyl glucoside and its molecular formula is shown in Figure 7 . MS diagrams and 1 H-NMR and 13 C-NMR spectra were shown in Supplementary Figures S31–S33 , respectively.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Data for compound 11 : white powder, m. p. 142–144°C; ESI-MS: Calcd for C 15 H 18 O 9 ([M-H] - ), 341.17; 1 H NMR (400 MHz, DMSO- d 6 ) δ : 7.55 (d, J = 15.8 Hz, 1H, H-7), 7.08 (d, J = 2.1 Hz, 1H, H-2), 7.01 (dd, J = 8.2, 2.0 Hz, 1H, H-6), 6.78 (d, J = 8.2 Hz, 1H, H-5), 6.26 (d, J = 15.9 Hz, 1H,H-8), 5.45 (d, J = 7.9 Hz, 1H), 5.28 (s, 1H), 5.06 (s, 2H,H-6′), 4.58 (s, 1H), 3.69–3.62 (m, 2H), 3.31–3.10 (m, 6H); 13 C NMR (100 MHz, DMSO- d 6 ) δ : 165.39 (C-9), 148.81 (C-4), 146.47 (C-7), 145.70 (C-3), 125.42 (C-1), 121.74 (C-6), 115.86 (C-5), 114.91 (C-8), 113.41 (C-2), 94.31 (C-1′), 77.86 (C-5′), 76.52 (C-3′), 72.56 (C-2′), 69.60 (C-4′), and 60.67 (C-6′). According to the abovementioned data and literature ( Dong et al, 2020 ), compound 11 was identified as 1-Caffeoyl glucoside and its molecular formula is shown in Figure 7 . MS diagrams and 1 H-NMR and 13 C-NMR spectra were shown in Supplementary Figures S31–S33 , respectively.…”
Section: Resultsmentioning
confidence: 91%
“…Data for compound 7 : pale yellow powder, m. p. 187–189°C; ESI-MS: Calcd for C 33 H 38 O 23 ([M + H] + ), 803.05; 1 H NMR (400 MHz, DMSO- d 6 ) δ : 12.56 (s, 1H, H-5), 8.93 (s, 1H, H-3′), 7.68 (d, J = 2.2 Hz, 1H, H-2′), 7.64 (dd, J = 8.6, 2.3 Hz, 1H, H-6′), 7.23 (d, J = 8.7 Hz, 1H, H-5′), 6.85 (d, J = 2.1 Hz, 1H, H-8), 6.46 (d, J = 2.1 Hz, 1H, H-6) , 5.56–5.44 (m, 4H), 5.30 (t, J = 2.4 Hz, 1H), 5.23 (d, J = 7.3 Hz, 2H), 5.09 (s, 3H), 4.97 (s, 1H), 4.87 (d, J = 7.1 Hz, 1H, H-1‴), 4.63 (t, J = 5.7 Hz, 1H), 4.31 (t, J = 5.8 Hz, 1H), 3.92 (d, J = 7.9 Hz, 1H), 3.77–3.70 (m, 2H), 3.59 (dd, J = 11.3, 5.0 Hz, 2H), 3.49 (d, J = 6.1 Hz, 2H), 3.26–3.15 (m, 7H), 3.10 (d, J = 4.1 Hz, 3H); 13 C NMR (100 MHz, DMSO- d 6 ) δ : 177.75 (C-4), 172.00 (C-6‴'), 162.68 (C-7), 160.85 (C-5), 156.07 (C-2), 156.07 (C-9), 147.67 (C-4′), 146.19 (C-3′), 134.16 (C-3), 124.33 (C-1′), 121.06 (C-6′), 116.64 (C-2′), 115.45 (C-5′), 105.81 (C-10), 101.48 (C-1‴), 100.65 (C-1″), 99.35 (C-1‴'), 99.20 (C-6), 94.33 (C-8),77.69 (C-5″), 77.26 (C-5‴), 76.50 (C-3″), 75.94 (C-3‴'), 75.83 (C-3‴), 74.85 (C-5‴'), 74.12 (C-2″), 73.26 (C-2‴), 72.80 (C-2‴'), 71.49 (C-4‴'), 70.00 (C-4″), 69.78 (C-4‴), 60.97 (C-6″), and 60.72 (C-6‴). According to the abovementioned data and literature ( Fossen et al, 2006 ; Dong et al, 2020 ), compound 7 was identified as Quercetin-3,7- O -diglucoside-4′- O -glucuronide and its molecular formula is shown in Figure 4 . MS diagrams and 1 H-NMR and 13 C-NMR spectra were shown in Supplementary Figures S19–S21 , respectively.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Dong et al [7] designed to isolate and identify the flavonoids and phenols from the aerial parts of Allium mongolicum Regel by using various chromatographic and spectrophotometric methods, a bioassay on motility of mouse isolated intestine tissue, as well as qualitative analysis using liquid chromatography/mass spectrometry (LC-MS). The aim of this study is to clarify whether these isolates have the effect of improving gastrointestinal function.…”
mentioning
confidence: 99%